Effect of sintering temperature on the microstructures and mechanical properties of sodalite infiltrate all-ceramic material for dental restorations - Naji, Ghassan Abdul Hamid; Omar, Ros Anita; Dabbagh, Ali; Yahya, Rosiyah (Taylor & Francis, 2018)
Potassium bromide sodalite (KBr-SOD) zeolite has been developed to enhance the mechanical properties of these restorations using a direct in situ hydrothermal condition followed by the sintering process. The purpose of this study was to determine the effects of sintering temperature on the microstructures and mechanical properties of porous alumina (A) and zirconia-toughened alumina (ZTA) discs infiltrated by KBr-SOD. Hundred and twenty disc-shaped samples were sintered at various temperatures and prepared for biaxial flexural strength and Vickers microhardness tests. The results showed that sintering temperatures from 1100 to 1600°C for both A-SOD and ZTA-SOD samples has resulted in a significant improvement in the density (2.8 and 1.1%, respectively), flexural strength (257 and 254%, respectively), Vickers hardness (109 and 112%, respectively), and Weibull modulus (7.5 and 3%, respectively). The present study concludes that infiltrated SOD material sintered at 1600°C is suitable for the fabrication of all-ceramic dental prostheses with adequate mechanical properties.